PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL - Tanata, Kelvin; Sudirgo, Tony (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this research is aims to analyze the effect of profitability, firm size, and business risk on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018 - 2020. The sample used in this research was 69 companies, selected by purposive sampling method and processed using the eviews 12 program. The result of the analysis shown that the profitability variable had no significant and positive effect on capital structure, the firm size variable had a significant and positive effect on capital structure, and the last variable, namely business risk, has no significant and negative effect on capital structure.